2022
DOI: 10.3389/fnut.2021.789006
|View full text |Cite
|
Sign up to set email alerts
|

Higher Yogurt Consumption Is Associated With Lower Risk of Colorectal Cancer: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background: Yogurt is known to be nutrient-rich and probiotic content, which gather optimism due to their potential role in preventing and managing cancers. The effect of yogurt consumption on colorectal cancer (CRC) is inconsistent.Objective: This study aims to investigate the association of yogurt consumption with the risk of CRC.Methods: Three databases, namely, PubMed, Web of Science, and Embase, were searched for all relevant studies from July 2021 on the association of yogurt consumption with CRC risk. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…The recent analysis of evidence from a European cohort confirmed a decreased risk of CRC linked to dairy food and calcium [5]. Sun et al recently reported an inverse relationship between yoghurt and CRC overall, despite the geographical stratification showing no significant association between dairy and CRC based on Asian studies [6].…”
Section: Introductionmentioning
confidence: 98%
“…The recent analysis of evidence from a European cohort confirmed a decreased risk of CRC linked to dairy food and calcium [5]. Sun et al recently reported an inverse relationship between yoghurt and CRC overall, despite the geographical stratification showing no significant association between dairy and CRC based on Asian studies [6].…”
Section: Introductionmentioning
confidence: 98%
“…Eating fermented foods has traditionally been associated with health benefits. In epidemiological studies, fermented dairy products have been associated with a reduced risk of metabolic syndrome [ 186 ], a reduced risk of obesity [ 200 ], a reduced risk of cardiovascular disease [ 201 ], and a reduced risk of colon cancer [ 202 , 203 ]. The consumption of fermented soybeans (miso and natto) has been associated with a reduced risk of hypertension [ 204 ] and a reduced cardiovascular risk [ 205 ].…”
Section: Fermented Food—sources Of Probiotics For Human Healthmentioning
confidence: 99%
“…While the overall microbiome effects of specific fermented products vary, yogurt consumption has been associated with decreased risk of several cancers [86,87]. A large meta-analysis has demonstrated that high yogurt consumption is associated with low colon cancer risk [88].…”
Section: Microbiome/dysbiosis and Crcmentioning
confidence: 99%